EFFECT OF CASTOR OIL AS POLYETHERETHERKETONE DENTURE BASE CLEANSER AGAINST CANDIDA ALBICANS COUNT AND SURFACE ROUGHNESS - WIJAYA, WILLIAM; TAMIN, HASLINDA Z.; CHAIRUNNISA, RICCA; HARAHAP, URIP (International Journal of Applied Pharmaceutics, 2025)
Objective: To evaluate the effectiveness of a 10% castor oil solution as a denture cleanser by comparing its ability to reduce Candida albicans counts and its effect on the surface roughness of thermoplastic nylon and polyetheretherketone (PEEK) denture base materials, relative to an alkaline peroxide cleanser. Methods: Thirty polished nylon and PEEK specimens (20 mm diameter, 2 mm thickness) were sterilized using ultraviolet (UV) light for 5 minutes and inoculated with Candida albicans (ATCC 14053). Specimens were then immersed for 20 minutes in one of the following solutions (n = 5 per group): A – Nylon + distilled water, B – Nylon + alkaline peroxide, C – Nylon + 10% castor oil, D – PEEK + distilled water, E – PEEK + alkaline peroxide, F – PEEK + 10% castor oil, Adherent cells were suspended and cultured on Sabouraud dextrose agar at 37 °C for 48 hours, after which colonies were counted. Surface roughness (µm) was measured using a profilometer before and after 122 hours of immersion in alkaline peroxide, 10% castor oil, or distilled water. Results: Alkaline peroxide produced the lowest Candida albicans counts; however, 10% castor oil resulted in a significantly greater reduction than distilled water. One-way ANOVA showed a highly significant effect of cleansers on Candida albicans counts for both nylon and PEEK specimens (p < 0.0001). For PEEK immersed in 10% castor oil, paired t-test analysis revealed no significant change in surface roughness (p = 0.061). Conclusion: The 10% castor oil solution effectively reduced Candida albicans counts and produced minimal changes in the surface roughness of PEEK denture base material. Castor oil shows promise as a biocompatible denture cleanser, with particularly favorable outcomes for PEEK-based dentures.